2018
DOI: 10.3390/technologies6040092
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2-Poly(3-Chloro-2-Hydroxypropyl Methacrylate) Nanocomposite for Selective Adsorption and Degradation of Dyes

Abstract: We report a new nanocomposite TiO2-poly(3-chloro-2-hydroxypropyl methacrylate) (TiO2-PCHPMA) for selective adsorption/degradation of cationic dyes and degradation of anionic dyes. TiO2-PCHPMA was prepared by free radical polymerization of CHPMA in the presence of TiO2 modified with 3-(trimethoxysilyl)propyl methacrylate. TiO2-PCHPMA adsorbed cationic methylene blue (MB), but did not adsorb anionic methyl orange (MO) in their aqueous solutions. The adsorption efficiency for MB reached 99% within 5 min at 28 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…These pollutants are bad for both human and animal health since they can lead to a variety of illnesses including poisoning of the central nervous system, skin rashes, kidney and liver damage, and blood abnormalities. The capacity of some processes, such as membrane separation, coagulation, oxidative remediation, and adsorption, to remove dyes from an aqueous medium makes them stand out. ,,,, Since there is a strong correlation between the quantity of surface area and the volume of the adsorbent, nanotechnology is effectively used in adsorption to purify water, and different nanomaterials have been promisingly used as adsorbents. , This results in a significant cost reduction that is directly connected to the lesser amount of adsorbent used. IONPs are one of the most often used nanomaterials because of how simple they are to synthesize and how many different chemicals they can uptake on their surface or in combination with other adsorbents. , …”
Section: Introductionmentioning
confidence: 99%
“…These pollutants are bad for both human and animal health since they can lead to a variety of illnesses including poisoning of the central nervous system, skin rashes, kidney and liver damage, and blood abnormalities. The capacity of some processes, such as membrane separation, coagulation, oxidative remediation, and adsorption, to remove dyes from an aqueous medium makes them stand out. ,,,, Since there is a strong correlation between the quantity of surface area and the volume of the adsorbent, nanotechnology is effectively used in adsorption to purify water, and different nanomaterials have been promisingly used as adsorbents. , This results in a significant cost reduction that is directly connected to the lesser amount of adsorbent used. IONPs are one of the most often used nanomaterials because of how simple they are to synthesize and how many different chemicals they can uptake on their surface or in combination with other adsorbents. , …”
Section: Introductionmentioning
confidence: 99%
“…Abdel-Bary et al, [25] studied graft copolymerization of polyacrylic acid onto gum acacia as a prospective candidate for removing of the dye methylene blue from aqueous system. Elbedwehy et al, [26] reported development of a graft copolymer of polyacrylonitrile and gum acacia using KMnO4/HNO3 redox pair as initiator. The adsorbent exhibited super adsorbent ability with adsorption capacity of 1017, 413 and 396 mg g -1 for Pb 2+ , Cd 2+ and Cu 2+ respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of nanotechnology has provided great opportunities for development of nanocomposite based adsorbents. Embedding magnetite nanoparticles (Fe3O4) in porous polymeric network of the hydrogel are attractive due to their recognized biocompatibility, sensitivity and rapid response to a remotely applied external magnetic field [27]. They can further expand the sorption capacity of hydrogel attributable to their nanoscopic size and the surface characteristics [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 We recently investigated TiO 2 modified with poly(3-chloro-2hydroxypropyl methacrylate) (TiO 2 -PCHPMA) (Figure 1) as an efficient material for rapid removal of MB either by adsorption or photocatalytic degradation under UV irradiation. 7 TiO 2 -PCHPMA consists of TiO 2 core with a size in a range of 15-45 nm covered by approximately 10wt% of the polymer layer. The TiO 2 cores are grains of primary TiO 2 nanoparticles with a size ranging from 1-8 nm.…”
mentioning
confidence: 99%